1981
DOI: 10.1073/pnas.78.9.5656
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic factors present in serum but not in plasma.

Abstract: In culture medium containing heparinized, heatinactivated, chicken plasma, normal chicken heart mesenchymal cells do not proliferate but their Rous sarcoma virus-infected counterparts proliferate maximally. In medium containing serum derived from chicken whole blood or plasma, on the other hand, normal chicken heart mesenchymal cells proliferate actively, at similar overall rates and to similar extents. The rate and extent of normal cell proliferation are decreased by a factor of approximately 'A with whole bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 26 publications
(20 reference statements)
0
10
0
1
Order By: Relevance
“…this appears to be due to the release of certain polypeptides from activated platelets during the clotting process (Balk et al, 1981;Gospodarowicz and Ill, 1980).…”
Section: B) Ethical Concerns and Animal Welfare Issuesmentioning
confidence: 99%
“…this appears to be due to the release of certain polypeptides from activated platelets during the clotting process (Balk et al, 1981;Gospodarowicz and Ill, 1980).…”
Section: B) Ethical Concerns and Animal Welfare Issuesmentioning
confidence: 99%
“…In the past, much effort was spent to identify the factors in serum that stimulate cell growth in vitro. An important step forward in the search for serum growth factors has been the finding that the most potent mitogenic factors present in serum are derived from activated thrombocytes (Balk et al, 1981;Gospodarowicz and Ill, 1980). Platelets are known to be a rich source of growth factors (Marx et al, 1998;Weibrich et al, 2002;Anitua et al, 2004), thus suggesting platelet lysates as a valuable animal serum substitute.…”
Section: Stimulation Of Erk1/2 Map Kinasesmentioning
confidence: 99%
“…However, the amount of autologous serum is limited, and a large part of it is needed for clinical applications. It has been suggested that the natural coagulated serum is more effective than plasma for cell proliferation due to the release of certain polypeptides and growth factors from activated platelets during the coagulation process [24,25]. Nevertheless, neither fresh serum nor natural coagulated serum are common and broadly available blood bank-derived products.…”
Section: Discussionmentioning
confidence: 99%